Microbial flora of odontogenic abscesses in pet guinea pigs. (1st October 2016) - Minarikova, A.; Hauptman, K.; Knotek, Z.; Jekl, V.
Abstract : Abscesses of odontogenic origin in guinea pigs pose a serious health problem and need to be treated with a combination of surgical and medical therapy. The aim of this prospective study was to describe the microbial flora of odontogenic abscesses associated with osteomyelitis in 24 pet guinea pigs, to perform antibiotic sensitivity testing, and to make recommendations for practitioners on the antibiotics of first choice. Inclusion criteria for the study included the animal being diagnosed with an odontogenic abscess which underwent surgery and was not pre‐treated with an antibiotic. Inclusion criteria matched for 24 guinea pigs. Samples (pus, capsule and affected tooth/bone) for bacteriological examination were collected under sterile conditions during the surgical procedure. The most commonly isolated bacteria from abscesses of odontogenic origin were Bacteroides fragilis in 12.8 per cent (6/47) of cases, Pasteurella multocida in 10.6 per cent (5/47) and Peptostreptococcus anaerobius in 8.5 per cent (4/47). Aerobic bacterial species only were isolated in 29.2 per cent (7/24) of cases, anaerobic bacteria only were isolated in 33.3 per cent (8/24), and mixed infection with anaerobic and aerobic bacterial species was seen in 37.5 per cent (9/24). Aerobes (n=20) were sensitive to enrofloxacin and marbofloxacin in 100 per cent of samples, benzylpenicillin potassium (penicillin G, PNCG) in 90 per cent, cephalotin in 85 per cent, amoxicillin‐clavulanate in 75 per cent, doxycycline in 70 per cent, gentamicin in 65 per cent and trimethoprim‐sulfamethoxazole in 55 per cent. Anaerobes (n=27) were sensitive to amoxicillin‐clavulanate in 100 per cent of cases, clindamycin in 96.3 per cent, metronidazole in 92.6 per cent, PNCG in 92.6 per cent and cephalotin in 74.1 per cent. As guinea pigs are strictly herbivorous animals, based on the results of this study the recommended antibiotic treatment for odontogenic abscesses is a combination of fluoroquinolones and metronidazole.